2009
DOI: 10.1007/s00253-009-2331-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding domains: multiplicity of biological roles

Abstract: Insoluble polysaccharides can be degraded by a set of hydrolytic enzymes formed by catalytic modules appended to one or more non-catalytic carbohydrate-binding modules (CBM). The most recognized function of these auxiliary domains is to bind polysaccharides, bringing the biocatalyst into close and prolonged vicinity with its substrate, allowing carbohydrate hydrolysis. Examples of insoluble polysaccharides recognized by these enzymes include cellulose, chitin, beta-glucans, starch, glycogen, inulin, pullulan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
267
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(279 citation statements)
references
References 65 publications
7
267
0
5
Order By: Relevance
“…Typically, glycoside hydrolases (GHs) that degrade complex polysaccharides possess carbohydrate-binding modules (CBMs) that promote enzyme-substrate proximity and thereby enhance catalytic efficiency [16,17]. Moreover, CBMs can also modulate the specificity and activity of cognate enzymes against plant cell wall Abbreviations AA, auxiliary activity; CAZy, carbohydrate-active enzymes; CBM, carbohydrate-binding module; DSC, differential scanning calorimetry; GH, glycoside hydrolase; ITC, isothermal titration calorimetry; LPMO, lytic polysaccharide monooxygenase; SBS, starch-binding site; SDS/PAGE, sodium dodecyl sulfate-polyacrylamide gel electrophoresis; b-CD, b-cyclodextrin.…”
Section: Abstract: Aa13;mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, glycoside hydrolases (GHs) that degrade complex polysaccharides possess carbohydrate-binding modules (CBMs) that promote enzyme-substrate proximity and thereby enhance catalytic efficiency [16,17]. Moreover, CBMs can also modulate the specificity and activity of cognate enzymes against plant cell wall Abbreviations AA, auxiliary activity; CAZy, carbohydrate-active enzymes; CBM, carbohydrate-binding module; DSC, differential scanning calorimetry; GH, glycoside hydrolase; ITC, isothermal titration calorimetry; LPMO, lytic polysaccharide monooxygenase; SBS, starch-binding site; SDS/PAGE, sodium dodecyl sulfate-polyacrylamide gel electrophoresis; b-CD, b-cyclodextrin.…”
Section: Abstract: Aa13;mentioning
confidence: 99%
“…Many industrial applications require the disruption of starch granules through hydrothermal, harsh chemical, or enzymatic treatments [11][12][13]. Despite development of relatively efficient a-amylases and other starch-degrading enzymes, there is still a significant margin for improving starch hydrolysis yields and shortening processing time, which would significantly reduce energy and costs of the process [14,15].Typically, glycoside hydrolases (GHs) that degrade complex polysaccharides possess carbohydrate-binding modules (CBMs) that promote enzyme-substrate proximity and thereby enhance catalytic efficiency [16,17]. Moreover, CBMs can also modulate the specificity and activity of cognate enzymes against plant cell wall Abbreviations AA, auxiliary activity; CAZy, carbohydrate-active enzymes; CBM, carbohydrate-binding module; DSC, differential scanning calorimetry; GH, glycoside hydrolase; ITC, isothermal titration calorimetry; LPMO, lytic polysaccharide monooxygenase; SBS, starch-binding site; SDS/PAGE, sodium dodecyl sulfate-polyacrylamide gel electrophoresis; b-CD, b-cyclodextrin.…”
mentioning
confidence: 99%
“…However, CBM20 and CBM21 families are proposed to form a common clan [23]. Analyses of threedimensional structures from many of these families showed a characteristic SBD fold of a distorted -barrel composed of several -strands and with one or, more frequently, two distinct binding sites that exhibit site-dependent modes of carbohydrate binding [25,26,[41][42][43].…”
Section: Carbohydrate Binding Modulesmentioning
confidence: 99%
“…Both families adopt a typical SBD fold (Boraston et al 2004;Guillen et al 2010) of distorted β-barrel (a β-sandwich) formed by 9 or 10 β-strands, as shown for solved three-dimensional structure of both modules present in the family GH13 maltohexaoseproducing amylase from Bacillus halodurans (Boraston et al 2006).…”
Section: Introductionmentioning
confidence: 99%